2020
DOI: 10.1108/jpcc-02-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Is distributed leadership an effective approach for mobilising professional capital across professional learning networks? Exploring a case from England

Abstract: PurposeThere is currently a focus on using networks to drive school and school system improvement. To achieve such benefits, however, requires school leaders actively support the mobilisation of networked-driven innovations. One promising yet under-researched approach to mobilisation is enabling distributed leadership to flourish. To provide further insight in this area, this paper explores how the leaders involved in one professional learning network (the Hampshire Research Learning Network) employed a distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Regarding the quantitative approach, only different types of surveys are observed. Finally, articles using the mixed method predominantly include case studies in which questionnaires, semi-structured interviews and observations are combined (Raza et al ., 2021; Brown et al. , 2021; Hernández and Navarro, 2018; Pino-Yancovic and Ahumada, 2020; Coenen et al ., 2021), or in which both student achievement level data and interviews are used (Eddy-Spicer, 2017; Chapman and Muijs, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the quantitative approach, only different types of surveys are observed. Finally, articles using the mixed method predominantly include case studies in which questionnaires, semi-structured interviews and observations are combined (Raza et al ., 2021; Brown et al. , 2021; Hernández and Navarro, 2018; Pino-Yancovic and Ahumada, 2020; Coenen et al ., 2021), or in which both student achievement level data and interviews are used (Eddy-Spicer, 2017; Chapman and Muijs, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Certain styles of leadership and school climate were found to favorably affect the innovative behavior of teaching staff ( Sagnak, 2012 ). Studies suggested that distributed leadership of school leaders played a crucial role in fostering innovative processes and guiding these initiatives ( Brown et al, 2020 ). It enables teachers to utilize their knowledge, passion, and imagination, which is vital to the success of educational improvements ( Fullan, 2007 ; Seashore Louis and Lee, 2016 ; Buske, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, teachers are engaged in decisions on which innovations to embrace and how to implement them, such as analyzing how new practices may be utilized to improve teaching and how to continue to use/refine teaching techniques over time ( Hallinger and Heck, 2010 ; Bush and Glover, 2014 ). For example, a case study in England revealed that if principals hold distributed leadership approaches, teacher professional learning network’s innovation would be positively supported ( Brown et al, 2020 ). Therefore, it can be hypothesized that principals’ distributed leadership may have a direct effect on teacher innovativeness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations